Making sense in sign : a lifeline for a deaf child - Froude, Jenny, 1939- (Parents' and teachers' guides ;, 2003)
Words were not enough for Tom; it was signs that made sense of a world silenced by meningitis. This work is an account by a woman of how her son contracted meningitis and of the deafness that resulted. It offers a discussion of the issues surrounding deafness from a parental viewpoint.